Mudança de base e o ensino das operações elementares - Ramos, Pamela Jéssika Balotin (2019)
Usual numbering system was modified over thousands of years in which we have a contribution of several people. Automated teaching through the use of algorithms to solve elementary operations without arouse reflexions about decimal basis utilized and positional numbering principle, leads us to difficulties within subsequent issues. The understanding of our numbering system features (decimal, positional, additive and multiplicative) is wanted for the teacher provides situations which your students make out necessary relations to discover and built mathematical concepts. Furthermore, the knowledge of alternative theoretical methodologies for teaching of mathematical concept is necessary because, in this case, we can point activities that make possible a consistent learning. In this sense, this work presents a review of numbering positional system (in every basis) pointing to initial basic education teachers. After this, we approach the Vah Hiele and Montessori theories for teaching and, this last, we foccus on basic operations (golden material). We aim reflections on teaching methodologies and, for this, we wished put together relevant informations of basic operations to primary teachers.